2020
DOI: 10.1253/circj.cj-20-0427
|View full text |Cite
|
Sign up to set email alerts
|

Novel Evaluation Method for Lower Extremity Peripheral Artery Disease With Duplex Ultrasound ― Usefulness of Acceleration Time ―

Abstract: Background: Duplex ultrasound scanning (DUS) plays a major role in less invasive diagnosis and assessment of lesion severity in lower extremity peripheral artery disease (PAD). In this study, we evaluated the efficacy of each DUS parameter measured in patients with PAD and established a simple method for PAD evaluation. Methods and Results:We retrospectively investigated 211 patients (270 limbs) who underwent assessment with both angiography and DUS. During DUS of the common femoral artery (CFA) and popliteal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…AT and maximal acceleration have long been described as predictive of severe arterial disease, particularly in renal artery stenosis, [27][28][29][30] but have recently come to the fore again, particularly in quantifying the severity of peripheral artery disease in carotid artery disease 31,32 and lower-extremity artery disease. 10,12,13,33 In this study, we confirm the great interest of this AT max in the diagnosis of either low TP or CLTI. In fact, we found almost the same cut-off value to detect TP ⩽ 30 mmHg or CLTI (212 ms and 213 ms, respectively), which is consistent with our previous study that found a threshold value of 215 ms. 10 Once again, AT max appeared to be the best predictor of TP ⩽ 30 mmHg, and also CLTI, in multivariate analysis highlighting its utility.…”
Section: Discussionsupporting
confidence: 81%
“…AT and maximal acceleration have long been described as predictive of severe arterial disease, particularly in renal artery stenosis, [27][28][29][30] but have recently come to the fore again, particularly in quantifying the severity of peripheral artery disease in carotid artery disease 31,32 and lower-extremity artery disease. 10,12,13,33 In this study, we confirm the great interest of this AT max in the diagnosis of either low TP or CLTI. In fact, we found almost the same cut-off value to detect TP ⩽ 30 mmHg or CLTI (212 ms and 213 ms, respectively), which is consistent with our previous study that found a threshold value of 215 ms. 10 Once again, AT max appeared to be the best predictor of TP ⩽ 30 mmHg, and also CLTI, in multivariate analysis highlighting its utility.…”
Section: Discussionsupporting
confidence: 81%
“…Acceleration time seems to be more and more described in the literature as associated with PAD. For example, in 2020, Yagyu et al published that the acceleration time ratio between the popliteal (or distal superficial femoral artery) and the common femoral artery was highly predictive of femoropopliteal artery lesions with an AUC of 0.93 ( 23 ). Recently, Sommerset et al described plantar acceleration time (PAT) as a novel predictor of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…With a cut-off value of 215 ms, AT allows for the detection of toe blood pressure ≤ 30 mmHg (one of the hemodynamic criteria of critical limb ischemia) with a 86% sensitivity and a 97% negative predictive value [12]. AT has also been reported as the most promising DW parameter for the prediction of femoropopliteal artery lesions: Yagyu et al showed that a common femoral to popliteal artery AT ratio of 1.25 or more was highly indicative of stenosis greater than 50% (confirmed by angiography), with a 86% sensitivity, a 92% specificity, and a 0.93 c-index [13].…”
Section: Measurement Methodsmentioning
confidence: 99%
“…In 1988, Handa et al proposed AT for the non-invasive diagnosis of renal artery stenosis, reporting that a cut-off value of 70 ms was highly predictive of a renal artery diameter reduction of 50% or more [14,15]. In these seminal studies, AT was described, with somewhat different wordings, as the time (in milliseconds) from the start of the systolic upslope to the apex of the systolic peak [10][11][12][13]. Unfortunately, referring to acceleration time or acceleration with vague definitions can be confusing [16].…”
Section: Measurement Methodsmentioning
confidence: 99%